Time course changes in corticospinal excitability during repetitive peripheral magnetic stimulation combined with motor imagery. (6th February 2022) - Asao, Akihiko; Wada, Kento; Nomura, Tomonori; Shibuya, Kenichi
Highlights: We provided peripheral magnetic stimulation (rPMS) combined with motor imagery (MI). Over 10 min of rPMS combined with MI facilitated corticospinal excitability. Combined rPMS and MI enhanced corticospinal excitability more than rPMS alone. Corticospinal changes during rPMS combined with MI were unrelated to MI ability. Abstract: Repetitive peripheral magnetic stimulation (rPMS) induces proprioceptive afferents and facilitates corticospinal excitability. Short-term sessions of rPMS combined with motor imagery (MI) enhance corticospinal excitability more than rPMS alone. However, it is not clear how long the intervention of rPMS combined with MI would be needed to facilitate corticospinal excitability. Therefore, we investigated the time course change in corticospinal excitability during the combination of rPMS and MI. Thirteen healthy volunteers participated in a 20-min intervention under the following three experimental conditions on different days: rPMS, MI, and rPMS combined with MI (rPMS + MI). In the rPMS and rPMS + MI, the participants were delivered rPMS, which was 25 Hz, 2 s/train at 1.5 × of the train intensity induced muscle contractions, through the wrist extensor muscles. In the MI and rPMS + MI, the participants repeatedly imagined wrist movements for 2 s. Motor evoked potentials (MEPs) were recorded from the extensor carpi radialis (ECR) and flexor carpi radialis (FCR) muscles every 5 min for each condition. The MEP amplitudes of the ECR after > 10 min of intermittent rPMS combined with MI were greater than baseline. The MEP amplitude of the ECR in rPMS + MI was greater than that in rPMS condition after 20 min of intervention. The present results suggest that over 10 min of intermittent rPMS combined with MI facilitates corticospinal excitability, and that the effect of rPMS combined with MI on corticospinal excitability might be greater than that of rPMS alone.